CRISPR/Cas9-mediated genome editing in vancomycin-producing strain Amycolatopsis keratiniphila - Hu, Mengyi; Chen, Shuo; Ni, Yao; Wei, Wei; Mao, Wenwei; Ge, Mei; Qian, Xiuping (Frontiers in Bioengineering and Biotechnology, 2023)
Amycolatopsis is an important source of diverse valuable bioactive natural products. The CRISP/Cas-mediated gene editing tool has been established in some Amycolatopsis species and has accomplished the deletion of single gene or two genes. The goal of this study was to develop a high-efficient CRISPR/Cas9-mediated genome editing system in vancomycin-producing strain A. keratiniphila HCCB10007. By optimizing the promoters which drove the expressions of scocas9 and sgRNA, the all-in-one editing plasmid by homology-directed repair (HDR) precisely deleted the single gene gtfD and inserted the gene eGFP with the efficiency of 100%. Furthermore, The CRISPR/Cas9-mediated editing system successfully deleted the large fragments of cds13-17 (7.7kb), cds22 (12.7kb) and cds22-23 (21.2kb) in ECO-0501 biosynthetic gene cluster (BGC) with high efficiencies of 81-97% by selecting the sgRNAs with the suitable PAM sequence. Finally, an even large fragment of cds4-27 (87.5kb) in ECO-0501 BGC was deleted by a dual-sgRNA strategy. The deletion of the ECO-0501 BGCs revealed a noticeable improvement of vancomycin production, and the mutants, which were deleted the ECO-0501 BGCs of cds13-17, cds22-23 and cds4-27, all achieved a 30%-40% increase in vancomycin yield. Therefore, the successful construction of the CRISPR/Cas9-mediated genome editing system and its application in large fragment deletion in A. keratiniphila HCCB10007 might provide a powerful tool for other Amycolatopsis species.